ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL CERITA DITINJAU DARI GAYA BELAJAR SISWA DI SMP NEGERI 5 SINJAI - Wahyudi, Gusti; Suriyati, Suriyati; Fitriani, Fitriani; Irmayanti, Irmayanti (UIN Imam Bonjol Padang, 2024)
Analysis of Students' Understanding of Mathematical Concepts in Solving Story Problems in View of Student Learning Styles at SMP Negeri 5 Sinjai. Sinjai Thesis: Mathematics Tadris Study Program, Faculty of Tarbiyah and Teacher Training IAI Muhammadiyah Sinjai, 2021. This research aims to describe: Students' understanding of mathematical concepts in solving story problems in terms of students' learning styles at SMP Negeri 5 Sinjai. This research is included in case study research using a qualitative approach. The subjects of this research were students of SMP Negeri 5 Sinjai class VII.1. The data collection methods are concept understanding tests and interview guidelines. Meanwhile, data analysis is carried out through data reduction, data presentation, and drawing conclusions. From the research results, a description of the understanding of mathematical concepts experienced by subjects with Visual, Auditory and Kinesthetic learning styles is obtained as follows: (1) Understanding of mathematical concepts in understanding problems, namely being able to understand the problem from the problem, being able to determine symbols that match the information known from the problem. , complete in writing down the information contained in the questions, and able to understand the concept; (2) Understanding mathematical concepts in planning problem solving, namely being able to determine mathematical concepts; (3) Understanding mathematical concepts in implementing problem solving plans, namely not being sure about the concepts or formulas used; (4) Understanding mathematical concepts in re-checking the solution obtained, namely knowing how to re-check it correctly.